HUBUNGAN ANTARA FREKUENSI MENGGUNAKAN ALCOHOL-BASED HAND RUB TERHADAP GAMBARAN KLINIS DERMATITIS KONTAK PADA TENAGA KESEHATAN DI RUMAH SAKIT MURNI TEGUH - JOICE SONYA GANI PANJAITAN; SUHARTOMI . (LP2MTBM MAKARIOZ, 2021)
Health workers in operating rooms and Intensive Care Units show high incidence of contact dermatitis, which was 18% to57%. Contact dermatitis in health workers occurs because there are many irritants in hospitals, one of them was antisepticsuch as hand sanitizer or hand rub. This study aimed to evaluate the relationship between the frequency of alcohol-basedhand rub application and the clinical presentation of contact dermatitis in health workers during the COVID-19 pandemic.This study was an observational study with a cross-sectional design. This study was performed among 111 health workers atMurni Teguh Hospital Medan from November 2020-March 2021 who were selected by the purposive sampling method.Meanwhile, the data analysis used to analyze the relationship between the frequency of Alcohol-Based Hand Rub applicationand the clinical presentation of contact dermatitis was the Fisher Exact Test. The majority of health workers at Murni TeguhHospital Medan used alcohol-based hand rub more than 10 times/ day (97.3%). Meanwhile, the clinical presentation ofcontact dermatitis found in health workers from the most to the least was dry skin as many as 103 people (92.8%), followedby thickened skin as many as 92 people (82.9%), burning sensation in 90 people (81.1 %), redness and itching in 88 people(79.3%), and pain in only 84 people (75.7%). After statistical analysis of the frequency of hand rub application and clinicalpresentations of contact dermatitis, no significant relationship was found (P value > 0.05). The frequency of alcohol-basedhand rub application did not affect the clinical presentation of contact dermatitis in health workers at Murni Teguh Hospital.